The Role of Academia and Headmaster to Enhance Overall Educational Quality in the Digital Era - Fathiah, Ainal Mardhiah, Salami Mahmud, Baihaqi, Yuswardi, Eliana, Miftahul Jannah (Bansigom Na Publisher, 2024)
The principal has a strategic function in the management of education. Principal learning leadership in the digital era, requires digital talents who are able to mobilize school residents to perform proportionally and professionally in accordance with their main duties and functions. Principals' learning leadership in the digital era must be a serious concern for the role of principals in order to be the driving force of teachers who compete with change. The principal, as a manager, has the responsibility of leading and bears full responsibility in the organization. Evaluation of international community service activities (PKM) is very important to measure the success and impact of these activities on the communities served. The resulting positive impact can be seen from the enthusiasm and appreciation shown by the Education Office Branch, Ministry of Religious Affairs Office, and School Principals throughout Central Aceh district.